Comparison of the trophic niches between two planktivorous fishes in two large lakes using stable isotope analysis. (October 2016) - Wedchaparn, Oranich; Zhao, Liangjie; Fan, Yingchun; He, Dong; Zhang, Hongyan; Ivan, Lori Nicole; Liu, Qigen; Ayisi, Christian Larbi
Abstract: This paper studied the sources of food and the trophic levels of silver and bighead carps using stable isotopes (δ 13 C and δ 15 N) analysis in Lake Qiandao and Lake Taihu. The δ 13 C values of POM and phytoplankton indicated that Particulate Organic Matter (POM) is of terrestrial origin in LQ and phytoplankton origin in LT. The different signature of δ 15 N of phytoplankton and POM also showed the different extent of anthropogenic impacts on the two lakes, with higher impacts in LT than in LQ. In LQ the trophic levels of silver and bighead carps were significantly different (2.48 ± 0.19 and 2.66 ± 0.19, respectively), while in LT the difference was not significant (2.15 ± 1.54 and 2.36 ± 0.38, respectively). Using a mixing model, we found that silver and bighead carps consumed a major proportion on phytoplankton and/or POM in both lakes with higher contribution of phytoplankton in more eutrophic lake. Silver and bighead carps had clear differentiation in food resources with silver carp more on POM and bighead more on zooplankton in deep and mesotrophic lakes. Contrary to this, both carps fed primarily on phytoplankton (and POM) and may have more niche overlaps in shallow and eutrophic lakes. Highlights: The δ 13 C values of POM and phytoplankton indicated that POM is of terrestrial origin in LQ and phytoplankton origin in LT. Silver and bighead carps consumed a major proportion on phytoplankton and/or POM in both lakes. Trophic levels of silver and bighead carps were significantly different in LQ but not in LT. Silver and bighead carps feed mainly on phytoplanktons.